1973
DOI: 10.1136/hrt.35.5.516
|View full text |Cite
|
Sign up to set email alerts
|

Adams-Stokes syndrome caused by paroxysmal third-degree atrioventricular block.

Abstract: Among I70 patients with Adams-Stokes syndrome, the majority had sinus rhythm between attacks. Clinical and electrocardiographic features of 67 patients in whom syncope was caused by paroxysmal third-degree atrioventricular block are discussed. The patients had normal pulse rates between attacks, their cerebral symptoms were usually not accompanied by cardiac symptoms, and 25 per cent had no symptoms suggesting heart disease. However, in 83 per cent the electrocardiogram showed constantly interventricular condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Several studies have shown that high-degree AV block is often initially intermittent and that a long time interval can elapse between the first symptomatic episode and the documentation of high-degree AV block [13, 24]. This was confirmed in the present study in which we found a median interval of 11 months between the index syncopal episode and the documented high-degree AV block.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown that high-degree AV block is often initially intermittent and that a long time interval can elapse between the first symptomatic episode and the documentation of high-degree AV block [13, 24]. This was confirmed in the present study in which we found a median interval of 11 months between the index syncopal episode and the documented high-degree AV block.…”
Section: Discussionsupporting
confidence: 90%
“…[8][9][10][11][12][13][14][15][16] Hypertension (78.20%) was the most common associated co-morbidity and 23.07% patients were diabetic, consistent with previous studies. …”
Section: Discussionsupporting
confidence: 83%
“…This seems a historically well-founded and clinically con venient terminology. Stokes-Adams syn drome is primarily a disease of the elderly and first becomes frequent in the 7th and 8th decades of life [4], The annual number of newly developed Stokes-Adams syndromes which require pacemaker implantation lies in the range of 100-150 per one million inhabitants.…”
Section: Stokes-adams Syndrome Due To Paroxysmal or Chronic Av Blockmentioning
confidence: 99%